Idolatría indígena y devoción criolla como respuestas a la variabilidad climática en Lima y Huarochírí durante el siglo XVIII - Carcelen Reluz, Carlos Guillermo (2007)
The existence ofreligious mantfestatians resultingfrom climatic phenomcna is constant. but wliat 11'C are going lo demonstrate is tite existence ofu widespread search of stability. Some invoke the Catholic God and saiuts looking for stability. an arder Wi¡JlOU/ alterations that allows the permanence of the political JI/dial/ body. Others invoke tite apus and {he Andean huacas lookiugfor tite restitution 01 their powet; tu the extent that (he pre-hispanic order presents u uuit betwcen wliat is human, whut is divine ami what is natural. Tlti: is translated in th« religious persccution throughout Colonial tintes despite whicl¡ tt survived adapting itsclfto the circumstances. but losing IIII/("h ot its anciem wisdom. such as thc necessary technology to Ioce tlte problems hrouglu bv the climatic voriabilitv